Nomad Science of Remote Intensities for Architectural Doctorates (EAAE Annual Conference Proceedings, 2023)
Nomad Science proposes the lived displacement of apparatuses of state science, drawing out and connecting knowledge systems. This production schema places architectural questioning as a free journey, aspiring towards a free subjectivity, accumulated through the nomadic search for distant knowledge fields as a creative project, to transform the nomadic into a new new science for architectural doctorates.